The Use of Sonification for the Analysis and Teaching of Interpretive Auditory Nuances - Kathleen Riley, (Frontiers in Neuroscience, 2022)
The integrative powers of human auditory perception in masterful performing artists can create nuances of sound from the interpretation of notes on a written page that often seem beyond one’s grasp as a listener. It is important to consider what type of feedback can provide a clearer understanding of nuances in sound to guide motor learning for the acquisition of new skills for expression. Master pianists’ performance has been used as a model for imitation. However, to ensure the accuracy of imitation and clear understanding, sonification was examined for its effectiveness in providing a more immediate understanding of individual interpretations in terms of inter-onset timing and velocity of the notes. Three master concert pianists volunteered to record a performance of the Chopin Nocturne Opus 15 No. 1 on a Yamaha Disklavier Pro MIDI (music instrument digital interface) grand piano. Logic software was used to analyze and compare MIDI data from each performance from the perspective of phrase-by-phrase, note onset timings, and corresponding data from the other pianists. The study objectives were to examine commonalities and differences in timing and dynamics among the performances using MIDI measurements; to probe whether listening to comparative performance data assisted with feedback from sonification would enhance music students’ understanding of the interpretive nuances through imitation; and to determine whether auditory-assisted sonification feedback could be used as a tool to expand students’ interpretive choices and enhance performance. Participants imitated selected phrases of each of the master pianists, first with only music listening, and then with feedback from the sonified, comparative performance data. Results showed limited success in attempts to imitate the model with auditory feedback alone. Auditory-assisted sonification feedback significantly enhanced the participants’ abilities to imitate the model faster and with greater accuracy in the final imitation experiments. Both quantitative and qualitative results from the study clearly showed the effectiveness of this kind of sonification as a feedback tool for heightening participants’ auditory understanding of nuances in sound, as well as providing an effective teaching tool for imitation exercises.